Cation transport in Escherichia coli. IX. Regulation of K transport (The Rockefeller University Press, 1978)
Kinetics of K exchange in the steady state and of net K uptake after osmotic upshock are reported for the four K transport systems of Escherichia coli: Kdp, TrkA, TrkD, and TrkF. Energy requirements for K exchange are reported for the Kdp and TrkA systems. For each system, kinetics of these two modes of K transport differ from those for net K uptake by K-depleted cells (Rhoads, D. B. F.B. Walters, and W. Epstein. 1976. J. Gen. Physiol. 67:325-341). The TrkA and TrkD systems are inhibited by high intracellular K, the TrkF system is stimulated by intracellular K, whereas the Kdp system is inhibited by external K when intracellular K is high. All four systems mediate net K uptake in response to osmotic upshock. Exchange by the Kdp and TrkA systems requires ATP but is not dependent on the protonmotive force. Energy requirements for the Kdp system are thus identical whether measured as net K uptake or K exchange, whereas the TrkA system differs in that it is dependent on the protonmotive force only for net K uptake. We suggest that in both the Kpd and TrkA systems formation of a phosphorylated intermediate is necessary for all K transport, although exchange transport may not consume energy. The protonmotive-force dependence of the TrkA system is interpreted as a regulatory influence, limiting this system to exchange except when the protonmotive force is high.